Single-Cell RNA Sequencing Reveals the Heterogeneity and Microenvironment of Temporal Bone Squamous Cell Carcinoma - Wen Lu; Binhong Liao; Zhuangzhuang Li; Yini Li; Jie Li; Linfei Mao; Tianjiao Zhou; Haibo Shi; Dongzhen Yu; Chuan Xu; Zhengnong Chen (Clinical and Experimental Otorhinolaryngology, 2026)
Objectives. Temporal bone squamous cell carcinoma (TBSCC) is the most common subtype of temporal bone malignancy. However, its low incidence, high misdiagnosis rate, and the difficulty of conducting large-scale studies and clinical trials have limited researchers’ understanding of its occurrence and progression, and diagnostic and therapeutic biomarkers remain lacking. Addressing these gaps requires a clearer understanding of TBSCC tumor heterogeneity and microenvironment. This study aimed to characterize the tumor heterogeneity and microenvironment of TBSCC.Methods. Single-cell RNA sequencing (scRNA-seq) is an effective approach for interrogating tumor heterogeneity. Here, we report scRNA-seq data for TBSCC. We collected and sequenced 113,344 cells from nine samples (five cancer tissues and four histologically verified adjacent normal temporal bone tissues) obtained from six patients with TBSCC.Results. The proportion of S-phase cancer cells was higher in samples with tumor invasion, and the pseudotime trajectory of cancer cells closely corresponded with the TBSCC differentiation level. We also detected higher communication intensity between certain immune cell pairs in cancer tissues than in histologically verified adjacent normal temporal bone tissues. In addition, we identified several cancer-related genes as potential diagnostic markers of TBSCC.Conclusion. This study is the first to characterize the complex heterogeneity and tumor microenvironment of TBSCC using scRNA-seq, providing new avenues for diagnosing, classifying, and treating this rare carcinoma.